KETERAMPILAN MENULIS NARASI DALAM BAHASA INGGRIS MELALUI TEKNIK MENULIS 5 FASE DAN ASESMEN KINERJA - Jenny Indrastoeti SP; Rukayah . (PGSD Universitas Negeri Medan, 2015)
This research aims to improve narration writing skills and the quality of learning English. Type of the research is a classroom action research consists of four components, namely planning, action, observation and reflection. The subjects were students S1 PGSD UNS, and the object was English learning process. The data analysis technique was an interactive analysis by performing data reduction, data display, drawing conclusions or verification and quantitative analysis. Result found that application of five-phases writing technique using performance assessment improved narration writing skills.